Differences in the intercorrelations of psychological characteristics in karate competitors and representatives - Ilievski, A. S.; Paskoski, I.; Kostovski, Z. (Sports Science and Health, 2026)
This research was conducted on a purposive sample of 32 respondents, 16 karate competitors and 16 karate national team members, men, seniors (according to WKF) from the Republic of North Macedonia. The main objective of this research was to determine the differences in the interrelations between the psychological characteristics of karate competitors and members of the karate national team. A total of 13 variables of psychological characteristics were used in the research: one variable for assessing general intellectual abilities, three variables for assessing specific intellectual abilities, six variables for assessing emotional characteristics, and three variables for assessing motivational dispositions. To determine the differences in the mutual relationships, first the intercorrelation matrices of the competitors and the national team members were calculated, then the Fisher transformed matrices were calculated, i.e. r1 and r2 - the correlation coefficients for each group, Z-statistics that measure the difference between the two correlation values and p-value - which determines whether the difference in the correlation is statistically significant. The results of the Z-test obtained in the study show statistically significant differences only in 5 pairs of variables from the two intercorrelation matrices.